Fiscal frameworks in the European Union: May 2012 update on priority countries- Addendum to: Occasional paper 91 (Luxembourg, 2012)
"This occasional paper is composed of fiches prepared by Commission services (Directorate-General for Economic and Financial Affairs) with a view to the interim peer review of national fiscal frameworks for five priority countries (Cyprus, Greece, Ireland, Latvia, Portugal), conducted under the auspices of the Economic Policy Committee in May 2012. These fiches are meant as an update and complement to the fiches released for these five countries as part of the main publication which accompanied the 2011 peer review."